Highly stretchable and oxidation-resistive Cu nanowire heater for replication of the feeling of heat in a virtual world - Kim, Dongkwan; Bang, Junhyuk; Lee, Wonha; Ha, Inho; Lee, Jinwoo; Eom, Hyeonjin; Kim, Myungsin; Park, Jungjae; Choi, Joonhwa; Kwon, Jinhyung; Han, Seungyong; Park, Hyojoon; et al. (Journal of Materials Chemistry A, 2020)
A thermal haptic device (THD) is used to implement temperature information in many virtual environments. The THD enables a user to feel the temperature as well as the thermal conductivity. Moreover, as temperature influences human emotion and preference, the THD enriches senses and experiences in a virtual environment. In this paper, we propose laser-assisted dual-function copper nanowire (CuNW) polyurethane acrylate (PUA) patterns for use as feedback controllable stretchable heaters as a 12-pixels THD, with highly enhanced mechanical and chemical durability. The CuNW-PUA pattern retains the stretchability from its serpentine mesh form, and the CuNW embedded in the PUA structure provides mechanical and chemical stability, facilitating a stable resistance. The CuNW-PUA pattern serves as a simultaneous heater and thermometer with accurate temperature control. Furthermore, the CuNW-PUA pattern is fabricated using a simple, fast, and elaborate laser process under ambient conditions. Finally, the CuNW-PUA pattern was used to realize heat transfer in various virtual environments in the form of 12-pixels on a nylon glove, showing potential for stretchable applications in next generation devices.
Keywords: Ambient conditions; Chemical durability; Copper nanowires; Laser-assisted; Polyurethane acrylates; Temperature influence; Temperature information; Virtual worlds